Improving Young Learners Vocabulary Mastery Through Game-Based Learning Using “MOFIN Mystery Box” - Fidyaningrum, Seftia Ani; Dewayanti, Shafira Artanita; Authar, Nailul (Universitas Nahdlatul Ulama Surabaya, 2021)
Teaching English as a foreign language is a challenge for all teachers, especially teachers who teach English for young learners. Despite so many challenges, English is highly recommended to be taught to children in primary schools. Teaching English to young learners must begin with an introduction to vocabulary. Vocabulary is the foundation and most important aspect of learning any language. The challenge of teaching English to young learners is the level of English proficiency of the teachers, as well as some new obstacles, particularly in terms of techniques policy, teaching English for young learners also requires creativity to make learning fun, because children enjoy having fun and playing and they also easily side-tracked, so teachers should choose teaching methods that are appropriate for their age group, game-based learning can improve students' vocabulary mastery, motivation, and interest in learning. Children employ their senses of smell, touch, taste, sight, and hearing to investigate the physical world holistically. Therefore, it would be better if children learn to use touchable games like “MOFIN Mystery Box”. The purpose of this study is to find out whether the “MOFIN Mystery Box” media can improve students' vocabulary mastery at Sukamanunggal State Elementary School. This research is qualitative research. Data collection techniques using observation. The data analysis techniques used in this study are identification, classification, and description. The result of this study is “MOFIN Mystery Box” can increase students’ vocabulary mastery at Sukomanunggal State Elementary School.